HUBUNGAN POWER OTOT LENGAN BAHU DAN KELENTURAN OTOT PUNGGUNG DENGAN HASIL TOLAK PELURU PADA ATLET PUTRA PPLP DISPORA RIAU - Rachman, Rama Wijaya; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on researcher's observation on PPLP athlete Riau Province has good posture but can not produce maximum repulsion, this can be seen from deficiencies when doing prefix, when holding bullet, exit position, arm strength and body position on When refused. The purpose of this research is to know the correlation of muscle power of shoulder arm and back muscle flexibility with repulsion result in putlet bullet athlete PPLP Dispora Riau. The population in this study is the male athletes PPLP Dispora Riau, amounting to 12 people. In this study the sample was taken using total sampling, it means that all the men's population is sampled as many as 12 people. The instrument is a test of two hand medicine ball put, sit and reach test and the result of bullets. The data obtained in the analysis by using the correlation produck moment simple and double. Based on the result of the research, it can be concluded that there is a power relationship between arm and shoulder muscles with the result of the shot hit at the athlete of PPLP Dispora Riau, where rhitung (0.778)> rtabel (0,602) at Î± = 0,05. There is a back muscle flexibility relationship with the result of a shot hit at the athlete of PPLP Dispora Riau, where rhitung (0.778)> rtabel (0,602) at Î± = 0,05. There is a mutual relationship between arm and shoulder muscle strength and back muscular flexibility of bullet outcome at the athlete of PPLP Dispora Riau, where rhitung (0.778)> rtabel (0.602) at Î± = 0.05.Keywords: Power Sleeve and Shoulder Muscle Muscle, Back muscle flexion, Bullet Reject Result